2000
DOI: 10.4049/jimmunol.164.4.1952
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric IgA Is Superior to Monomeric IgA and IgG Carrying the Same Variable Domain in Preventing Clostridium difficile Toxin A Damaging of T84 Monolayers

Abstract: The two exotoxins A and B produced by Clostridium difficile are responsible for antibiotic-associated enterocolitis in human and animals. When added apically to human colonic carcinoma-derived T84 cell monolayers, toxin A, but not toxin B, abolished the transepithelial electrical resistance and altered the morphological integrity. Apical addition of suboptimal concentration of toxin A made the cell monolayer sensitive to toxin B. Both toxins induced drastic and rapid epithelial alterations when applied basolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 73 publications
5
76
0
Order By: Relevance
“…Similar in vitro models have been used previously to compare the neutralizing function of antigen-specific monoclonal IgG and IgA/SIgA (31,39,40). Although one has to acknowledge that the Caco-2 cell line may not recapitulate all functions of normal intestinal epithelial cells, their pattern of cytokines following exposure to S. flexneri was consistent with that of other cell lines and that found in vivo (41,42).…”
Section: Discussionsupporting
confidence: 50%
“…Similar in vitro models have been used previously to compare the neutralizing function of antigen-specific monoclonal IgG and IgA/SIgA (31,39,40). Although one has to acknowledge that the Caco-2 cell line may not recapitulate all functions of normal intestinal epithelial cells, their pattern of cytokines following exposure to S. flexneri was consistent with that of other cell lines and that found in vivo (41,42).…”
Section: Discussionsupporting
confidence: 50%
“…Fractionation of pIgA and mIgA Present in Plasma-derived Preparations-Size exclusion chromatography is a robust technique to separate pIgA from mIgA recovered from hybridoma cell supernatants (15) and from cell clones engineered to produce IgA (26). Two different resins and column sizes were used in the present study.…”
Section: Plasma-derived Iga and Igm Both Bind To Immobilized Hsc In Vmentioning
confidence: 99%
“…A combination of equimolar amounts of purified pIgA and hSC (IgAPCG-4) or mSC (IgA7D9 and IgAC5) for 1 h at room temperature resulted in the formation of covalent heterodimer complexes, as indicated by the detection of shifted SC to the position of pIgA (lanes 3, 6, and 9) when the protein was analyzed under nonreducing conditions. As reported previously, the percentage of covalence varied from one pIgA to another (11,25) as reflected by the appearance of free SC migrating as a band of 80 kDa. When loaded onto a molecular sieving column run in PBS, co-elution of SC and pIgA confirmed that the two proteins were indeed associated in the form of covalent and noncovalent SIgA complexes (15) (data not shown).…”
Section: Resultsmentioning
confidence: 81%
“…100 ng of C. difficile toxin A was mixed with 50 ng of either pIgAPCG-4 or SIgAPCG-4 permitting neutralization in in vitro assays (11). 60 ng of purified rotavirus was incubated with 100 ng of either pIgA7D9 or SIgA7D9 in PBS for 2 h at room temperature, corresponding to ϳ160 Ab molecules/virus (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation